Closing the gap: There is a gap, and it is not going away. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This paper aims to examine the vast and growing body of evidence which shows that workplace innovation, practices which empower employees to make day-to-day-decisions, challenge established practices and contribute ideas, which are heard at the most senior levels of an organisation lead to better business results as well as enhanced workforce health and engagement. Design/methodology/approach: – As European businesses struggle to emerge from recession, this evidence offers an important resource for enhanced competitiveness, increasing productivity and the rate of innovation. Findings: – However, the article also looks at why most businesses are either unaware of this evidence, or that they are unable or unwilling to act on it. Successive surveys demonstrate a substantial gap between research evidence of "what works" and common workplace practice. Originality/value: – The practical challenge is to build the conditions at European, national and local levels which stimulate, resource and sustain workplace innovation on a large scale. This is vital for European competitiveness as well as for the well-being of Europe's workers, but it means nothing less than redefining the "common sense" view of the world experienced by managers and others who influence the nature of the workplace. It also implies the creation of a public sphere of shared knowledge and experience, freely available to those instigating or informing change.